Women in Civil War Texas : Diversity and Dissidence in the Trans-Mississippi - Liles, Debbie M.; Boswell, Angela, 1965- (Book collections on Project MUSE., 2016)
"Women in Civil War Texas is the first book dedicated to the unique experiences of Texas women during this time. It connects Texas women's lives to southern women's history and shares the diversity of experiences of women in Texas during the Civil War. Contributors explore Texas women and their vocal support for secession, coping with their husbands' wartime absences, the importance of letter-writing, and how pro-Union sentiment caused serious difficulties for women. They also analyze the effects of ethnicity, focusing on African American, German, and Tejana women's experiences. Finally, two essays examine the problem of refugee women in east Texas and the dangers facing western frontier women"--Publisher's website.